Regulatory and financial burdens of EU legislation in four Member States – a comparative study. Vol. 2: Burdens arising from the Posting of Workers Directive - Lukas Harta; Marion Jousseaume; Matthias Kullas; Lavinia Petrache; Andrea De Petris; Jan Tiessen; Lorenz Löffler; Paul Braunsdorf; Pia Czarnetzki; Jessica Catalano; Louis Colnot; Matteo Pedralli (Foundation for Family Businesses, 2023)
The research project on the costs of bureaucracy extends to four volumes on four different regulations. Part two is dedicated to the posting of workers. Here the information required when applying for such a certificate in four member countries of the EU was examined along with the economic costs to companies that result in practice. – – Das Forschungsprojekt "Bürokratiekosten" erstreckt sich über vier Bände zu vier verschiedenen Regulierungen. Teil 2 widmet sich der Entsenderichtlinie. Hier wurden die für den Antrag erforderlichen Angaben in vier Mitgliedsländern der EU untersucht und die ökonomischen Kosten in der Unternehmenspraxis.
Keywords: 330